IDEAL PRIMA FUZZY DI SEMIGRUP S - Abdurahim Abdurahim (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2017)
A fuzzy membership function is a function that maps the nonempty set  to a closed interval . Furthermore, if the function domain is replaced with a semigroup, then the function is called fuzzy subset. A fuzzy subset mapping  to  is denoted by . A fuzzy subset  is called fuzzy ideal if it satisfies both  and . Moreover,  is called a fuzzy prime ideal if for any fuzzy ideal  and , with  implies  or . In this paper be investigated about some characteristics of prime fuzzy ideals and some example of them.